Effects of aluminium content on the molecular structure and properties of polyaluminocarbosilane for SiC fibre fabrication. Issue 13 (September 2019) - Duan, Yangpeng; Mo, Gaoming; Huangfu, Zhiyun; Liang, Yanqin; Cui, Zhenduo; He, Liu; Huang, Zhengren; Chai, Zhifang; Huang, Qing
Abstract: Polyaluminocarbosilane (PACS) is an important precursor for silicon carbide (SiC) fibres and ceramics. Much work has focused on the sintering effect of elemental Al, and it was found to increase density and inhibit grain growth during the pyrolysis of the SiCx Oy phase at high temperatures. In addition to the sintering effect, Al may also affect the detailed molecular structure and the related properties of the precursor. In this work, PACS with different Al contents are prepared by a high-pressure method. The structural forms of the component elements are quantitatively determined by 1 H NMR, 29 Si NMR, DEPT, 27 Al MAS NMR and elemental analysis, and a method of determining the relative branching degree of PACS is proposed. It is found that increasing the Al content in the precursor leads to an increase in the weight percentage of the SiC3 O, CH2 and CH groups, while the content of the SiC4 groups remains almost unchanged, which consequently causes a rise in the relative branching degree of the molecular structure. The rheological properties of the precursors are investigated on a monofilament spinning device. It is found that the apparent viscosity rises, and the spinnability of the precursor weakens, with increasing Al content, while the non-Newtonian index becomes larger, indicating a decrease in the pseudo-plasticity of the precursor. In addition, the ceramic yield becomes higher, which is definitely correlated to the more branched and ring molecular structures.